Buried umbilicus with inflammation due to retained rubber foreign body after liposuction: A case report. Issue 25 (June 2018) - Kim, Jong-Lim; Shin, Jin Yong; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Abstract: Introduction: Liposuction is one of the most widely performed aesthetic surgeries. It is mainly used for the correction of deep and superficial fat accumulations and remodeling of the body contour. Case presentation: We present a rare case of unusual rubber foreign body found within the periumbilical area during the reconstruction of buried umbilicus after liposuction. A 61-year-old female had undergone a liposuction surgery 10 years ago. Last year, she experienced signs of inflammation around the periumbilical area. The patient was treated with antibiotics and daily dressing at a local clinic. However, her symptoms did not improve with treatment. After admission, we decided to reconstruct the umbilicus and explore the previous operative site. During reconstruction of umbilicus, we finally discovered a rubber foreign body in the periumbilical area and buried umbilicus. Conclusion: Retained surgical foreign body can clinically manifest as acute reaction, such as an inflammatory response, infection, or abscess within days or weeks after the operation. Patients may complain of pain and discomfort, even months or years after the procedure. Our patient had suffered from delayed inflammation due to retained surgical foreign body after liposuction surgery. We emphasize the need for excellent communication within the surgical team to prevent the incidence of retained surgical bodies.